PERILAKU MAHASISWA DALAM PEMBELAJARAN PRAKTIK KLINIK KEPERAWATAN ANAK - Theresia Titin Marlina (Jurnal Keperawatan Notokusumo, 2017)
Background : Learning nursing clinical practice is a form of learning that is carried out in an order of health aimed to foster attitudes and professional skills. Clinical practice is essential to prepare students to become a profesional nurses. Method : This research is qualitative with the aim to describe the behavior of students in the children learning of nursing clinical practice. The method used are observation and interviews with 9 students and 2 clinical instructor, obtained by accidental sampling. Results : Preparation of students practice doing is preparing the syllabus, materials and a list of competencies. Strategy competency achievement by drafting a plan of activities every day, communicating with the supervisor, actively courting the bell, high willingness to help perform nursing care, take action in accordance habit in the hospital, kee ping discipline. Conclusions : Student behavior in nursing clinical practice children's learning is good. Preparations have been made, caring behavior has been applied and the learning objectives achieved full.